Pedal Powered Water Pump Application To Support Irrigation Activities In Carat Village, Gempol District, Pasuruan Regency, East Java Province - Hatta Hatta; Mochammad Mochammad; Tjahjani IK; awang wicaksono (OJS Universitas Muhammadiyah Gresik, 2019)
In this PKM program, our partner is a fruit farmer in Carat Village, which is the name of a village in GempolDistrict, Pasuruan Regency, East Java Province. This village actually has the opportunity to develop in the plantation sector with its main plants cucumber, cantaloupe, cucumber mas, and roses. However, it is constrained by the condition of very barren rice fields and plantations covering an area of 60 hectares, due to the lack of support for the local irrigation system currently being implemented. Based on interviews and observations in the field, there are 2 main focuses of the problems currently faced by partners, namely: 1) The production sector is caused by the large amount of energy that must be spent to drawwater from the well with the distance of the water source to the plantation using simple equipment and 2). Field of management due to the under-optimal distribution of crop yields and monitoring functions of yields in each period. Some of the things planned by the PKM team are innovating bicycles which are named pedal power as plantation irrigation equipment and solutions in the field of production, as well as providing training and mentoring in financial reporting as a solution in the field of management. The purpose of this activity is to realize a system improvement, increase crop production, and create effective, efficient and competitive management. This activity was realized with an approach in the form of making a sustainable cooperation program untilthe end of PKM, creating a family atmosphere between the two and understanding that the problems experienced werea shared problem so that they could be solved together according to the level of responsibility to achieve the expectedbenefits, namely increased yields, production and productivity and competitiveness, independence and welfare of thecommunity.